Pelatihan Layanan Konseling Individual Bagi Guru Bimbingan dan Konseling - Heni Sulusyawati; Juwanto Juwanto (Universitas Prof. Dr. Hazairin, SH, 2020)
In this globalization era, the role of the concept in schools is very important. Therefore, this individual counseling training activity was carried out. This individual counseling service training activity was aimed to increase the understanding of counselors at Muhammadiyah Integrated Junior High School Bengkulu in conducting individual counseling. The methods used in this training were lectures, questions and answers, discussions, and practices. Participants involved in this training were counselors at Muhammadiyah Integrated Junior High School Bengkulu. The results of the training for individual counseling services went well, they were shown from the results of the questionnaire before being given training for individual counseling services in the category of not understanding with a percentage of 28.70%. After the training in individual counseling services was given to the students, there was enhancement in understanding of counselors in conducting individual counseling. They were in understanding category, and they were able to do good counseling practices with an achievement percentage of 89.81%.